Atmospheric river lifecycle characteristics shaped by synoptic conditions at genesis. (12th July 2021) - Kim, Sol; Chiang, John C. H.
Abstract: The range of synoptic patterns that North Pacific landfalling atmospheric rivers form under are objectively identified using genesis day 500 hPa geopotential height anomalies in a self‐organizing map (SOM). The SOM arranges the synoptic patterns to differentiate between two groups of climate modes—the first group with ENSO (El Niño Southern Oscillation), PDO (Pacific Decadal Oscillation), PNA (Pacific North American) and NP (North Pacific index) and the second group with AO (Arctic Oscillation), EPO (East Pacific Oscillation), and WPO (West Pacific Oscillation). These two groups have their positive and negative modes organized in opposite corners of the SOM. The ARs produced in each of the synoptic patterns have distinct lifecycle characteristics (such as genesis and landfall location, duration, velocity, meridional/zonal movement) and precipitation impacts (magnitude and spatial distribution). The conditions that favour AR trajectories closer to the tropics tend to produce higher amounts of precipitation. The large‐scale circulation associated with AR genesis shows a close relationship between the genesis location and the location and intensity of the upper‐level jet in the west/central pacific as well as anomalous, low‐level southwesterly winds in the east pacific. Abstract : The range of synoptic patterns that North Pacific landfalling atmospheric rivers form under are objectively identified using genesis day 500 hPa geopotential height anomalies in a self‐organizing map. The nine identified synoptic patterns produce ARs with distinct lifecycle characteristics (such as genesis and landfall location, duration, velocity, meridional/zonal movement) and precipitation impacts (magnitude and spatial distribution).